The Long Journey to BVD Eradication - Volker Moennig; Matt J. Yarnall (Pathogens, 2021)
This paper provides a short review of bovine virus diarrhoea (BVD) control programmes across Europe, with a particular focus on current efforts from a stakeholder perspective. Using outputs gained from a global, virtual congress on BVD control, the theory of the journey from BVD control to possible eradication is enriched with insight from stakeholders representing the major parts of the cattle industry. Current control programmes were presented by Javier Dieguez (Galicia), Neil Shand (England), Neil Paton (Wales), Jenny Purcell (Scotland), Maria Guelbenzu (Ireland), Jörn Gethmann (Germany), and Matthias Schweizer (Switzerland).